Information Verification Processes In Traffic Reporting Through Citizen Journalism - Aditia Daka Pratama; Dilmai Putra; Bayu Risdiyanto (Multidisciplinary Journals, 2026)
This study aims to analyze information verification processes in traffic reporting produced through citizen journalism practices. The increasing reliance of the public on fast and real-time information highlights the need for proper verification mechanisms to ensure that disseminated information remains accurate, balanced, and ethically responsible. This research employs a qualitative descriptive approach using content observation, in-depth interviews, and documentation techniques. The analytical framework is based on journalistic verification principles that emphasize accuracy, completeness of information, ethical considerations, and public responsibility. The findings indicate that information verification is conducted through several stages, including checking the completeness of basic data, assessing the relevance and timeliness of events, and applying ethical judgment prior to publication. Information that does not meet verification standards tends to be excluded, even when it originates from public contributions. These results suggest that citizen journalism has strong potential as a credible source of public information when supported by consistent and responsible verification practices. This study contributes to communication studies by strengthening the understanding of verification mechanisms within citizen journalism, particularly in the context of traffic reporting.